Test of mathematics at the 10 + 2 level - Indian Statistical Institute; Bandyopadhyay, Pradipta (New Delhi : Affiliated East-West Press, 2018)
The multiple-choice and short-answer type tests for B.Stat. (Hons.) and B.Math. (Hons.) admission in 2008-17 have been included in the seventeenth edition.
Keywords: Psychological testing